Regiões de estabilidade no ambiente de um sistema de asteroide triplo - Heringer, Alzenir Eduardo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work was developed from the study by Araujo, R.A.N. et al. Stability regions around the components of the triple system 2001 SN263. (Monthly Notices Of The Royal Astronomical Society, 2012, v. 423(4), 3058-3073 p.) where it was studied the stable and unstable regions system (2001 SN263), which is a triple asteroid system, and these are celestial orbiting our sun. Being close to the Earth is characterized as NEA (Near-Earth Asteroids), asteroids and which periodically approach the Earth's orbit, given that there is great interest in the study and exploitation of these objects, it is the key can carry features that contribute to better understand the process of formation of our solar system. Study the dynamics of bodies that govern those systems proves to be greatly attractive because of the mutual gravitational perturbation of bodies and also by external disturbances. Recently, NEA 2001 SN263 was chosen as a target of Aster mission where a probe is sent for this triple system, appearing therefore the need for obtaining information for characterizing stable regions internal and external to the system, with respect to the effects of radiation pressure. First, this study demonstrated that the integrator used showed satisfactory results of the orbital evolution of bodies in accordance with previous studies and also the characterization of stable and unstable regions brought similar results to the study by Araujo et al. (2012). From these results it was possible to carry out the implementation of the radiation pressure in the system in 2001 SN263, in a region close to the central body, where the simulations were carried out, which brought as a result that the regions before being characterized as stable in unstable true for small particles size from 1 to 5 micrometers. So the next orbital region to the central body and the ... ( Complete abstract click electronic access below)

Este trabalho foi desenvolvido a partir do estudo realizado por Araujo, R.A.N. et al. Stability regions around the components of the triple system 2001 SN263. (Monthly Notices Of The Royal Astronomical Society, 2012, v. 423(4), 3058-3073 p.) onde foi estudado as regiões estáveis e instáveis do sistema (2001 SN263), que é um sistema triplo de asteroides. Estes são corpos celestes que orbitam nosso Sol e que se aproximam periodicamente da órbita da Terra, sendo por isso caracterizados como NEAs (Near-Earth Asteroids). Em virtude disso, existe grande interesse no estudo e exploração destes objetos, que por serem primordiais podem carregar características que contribuiriam para entendermos melhor o processo de formação de nosso sistema solar. Estudar a dinâmica dos corpos que regem esses sistemas mostra-se grandemente atraente devido à perturbação gravitacional mútua dos corpos e também por perturbações externas ao sistema. Recentemente, o NEA 2001 SN263 foi escolhido como alvo da missão ASTER, onde uma sonda será enviada para este sistema triplo, surgindo, portanto, a necessidade de se obter informações para se caracterizar regiões estáveis internas e externas ao sistema, com relação aos efeitos da força de radiação solar. Primeiramente, este trabalho demonstrou que o integrador usado apresentou resultados satisfatórios da evolução orbital dos corpos de acordo com os estudos anteriores e também a caracterização das regiões estáveis e instáveis trouxeram resultados semelhantes ao estudo de Araujo et al. (2012). Diante desses resultados foi possível realizar a implementação da força de radiação solar no sistema 2001 SN263, em uma região próxima ao corpo central, onde foram realizadas as simulações, as quais trouxeram como resultados que as regiões antes caracterizadas como estáveis ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Asteroides; Radiação solar; Pirolise; Tires Recycling